Analysis lean and green manufacturing in the ship production process at PT XYZ - Agustin, Alika Kurnia; Widjajati, Endang Pudji (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
The manufacturing industry, especially in sectors like shipbuilding, is experiencing rapid growth and heightened competition, necessitating ongoing enhancements in productivity and operational efficiency. PT XYZ, a prominent shipyard in Indonesia, is dedicated to advancing its business operations, which include new ship construction, maintenance, repair, and engineering consultancy. Despite these efforts, the company faces significant challenges in optimizing production processes, resulting in inefficiencies and potential delays in project delivery. This study examines waste in ship production processes at PT XYZ using lean manufacturing principles and proposes strategies for waste reduction through green manufacturing approaches. By identifying and addressing issues such as waiting times and inventory waste in fabrication workshops, the research seeks to boost operational efficiency and secure a competitive edge in the shipbuilding industry. The results reveal that implementing targeted improvements using VALSAT and other lean methodologies has markedly enhanced system efficiency. The identification and rectification of waste sources have led to increased production efficiency and improved product quality, demonstrating the effectiveness of these lean strategies in refining manufacturing operations.